A study on the demograpidc profiles, disease characteristics and one-week outcome of red-tag patients in the emergency department, Hospital Universiti Sains Malaysia - Rahmat, Rashdan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2007)
INTRODUCTION: Emergency Department provides initial treatment to patients with a broad spectrum of life threatening illnesses and injuries. Unfortunately, we hardly can found literatures discussing the distribution of red tag patients and their one week outcome. METHODOLOGY: A prospective observational study for a period of 6 months was carried out. The variables include age, sex, race, type of cases, shock index (SI), revised trauma score (RTS) and mortality. univariate analysis was done to find possible predictors of mortality. RESULTS: A total case was 440, 101 patients (23.0%) were trauma cases and 339 patients (77.0%) were non traum~ cases. The mean age of the population is 4 7.21 ± 21.77 5 and ranges from 1 to 89 years old. For trauma cases, the mean age for population of patients was 31.61 ± 21.411 years old. About 2/3 of the patients were male (67.27%). More than half of the cases (58.6%) were medical cases, being cardiac or non cardiac in origin. Twenty seven patients (6.13%) died within a week. From univariate analysis, high score of RTS and shock indek are associated with one week mortality for trauma and medical cases respectively (p<O. 01 ). CONCLUSIONS: There was more medical than trauma red tag patients. RTS and SI are very useful in assessing the prognosis of trauma and non trauma cases respectively.